Numerical study on heat transfer and pressure drop characteristics of fluid flow in an inserted coiled tube type three fluid heat exchanger. Issue 4 (12th March 2019) - Mohapatra, Taraprasad; Ray, Subhankar; Sahoo, Sudhansu Sekhar; Padhi, Biranchi Narayana
Abstract: The paper presents numerical investigations of a three fluid heat exchanger (TFHE), which is an improvement on the double pipe heat exchanger, where a helical tube is inserted in the annular space between two straight pipes. The helical tube side fluid, that is, hot water continuously transfers heat to the outer annulus side fluid and innermost tube side fluid. The heat transfer and pressure drop characteristics of the TFHE are assessed for different flow rates and inlet temperatures. With an increment in the volumetric flow rate of the helical tube side fluid and outer annulus side fluid, the overall heat transfer coefficient increases, and the effectiveness decreases for heat transfer from the helical tube side fluid to outer annulus side fluid in both parallel flow and counter flow configurations. It is also observed that with increment in the helical tube side fluid inlet temperature, the overall heat transfer coefficient and effectiveness increases for heat transfer from the helical tube side fluid to outer annulus side fluid in both flow configurations. The parameter, JF factor, has been proposed to evaluate the thermohydraulic behavior of the TFHE, where it is obtained that the behavior of the TFHE is better at a lower helical tube side fluid velocity and higher outer annulus side fluid velocity.